Iron-Deficiency Anemia Related to Ancylostoma duodenale Infection in 67 Years Old Female Patient - Widodo Adi Prasetyo; Armen Ahmad (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background. Ancylostomiasis is an infection caused by hookworms. It is estimated that hookworms infect 1.2 billion people worldwide and cause higher morbidity than other types, mainly due to iron deficiency anemia. Hookworm infection increases with age. The main clinical manifestations are abdominal pain, features of iron deficiency anemia and hypoproteinemia. Diagnosis is based on the finding of characteristic eggs in the stool. Case presentation. A 67-year-old female patient had been administered into the Internal Medicine Ward of Dr. M. Djamil Padang Hospital with the main complaint of weakness, fatigue, and lethargy which had increased since 3 days before being admitted to the hospital. The patient also had complaints of pale skin, fever, heartburn, decreased appetite and weight loss. The patient was admitted to the hospital with awareness of compost mentis, cooperative, and his general condition appeared to be moderately ill, blood pressure 130/90 mmHg, pulse rate 104 x/minute, regular pulse, adequate filling, respiratory rate 22 x/minute, temperature 37.8 C. On physical examination, the conjunctiva of the pantient’s eyes were anemic. Laboratory examination revealed Hemoglobin 4 g/dl, Hematocrit 16%, MCV/MCH/MCHC 62fl/15pg/25g/dL, Reticulocytes 0.5%, SI/TIBC 22/315 mg/dL, Ferritin 8.5 ng/mL, and peripheral blood smear showing severe hypochromic microcytic anemia and relative eosinofilia. Ancylostoma duodenale worm eggs were found on routine stool examination. Final diagnosis was Severe microcytic hypochromic anemia caused by an iron deficiency and Ancylostomiasis. Severe microcytic hypochromic anemia caused by iron deficiency and ancylostomiasis was established based on the patient’s history, physical examination and laboratory investigations. Conclusions. Hookworms infect many people worldwide and cause high morbidity, mainly due to iron deficiency anemia. The highest prevalence is found in the tropics and subtropics, including Indonesia. The main clinical manifestations are abdominal pain, features of iron deficiency anemia and hypoproteinemia. Diagnosis is based on the finding of characteristic eggs in the stool. Albendazole 400 mg single dose resulted in 80% cure and a dose of 200 mg/day for 3 days gave 100% cure. Treatment of anemia is by administering ferrous sulfate or ferrous gluconate orally 200 mg three times a day and continued for up to 3 months after normal hemoglobin levels are achieved to maintain iron stores.